Pemenuhan Nafkah Bagi Pasangan Mental Retardation di Desa Sidoharjo Kecamatan Jambon Kabupaten Ponorogo Perspektif Keadilan Gender dalam Islam - Meilinda, Fauziyah Putri (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
In a marriage bond produces a legal consequence, namely rights and obligations.One form of the husband's obligation to his wife is maintenance. This maintenance obligation is not determined by how much the wife and household needs, but is adjusted to the ability of the husband as the head of the household to meet his needs, as is the case with marriages carried out by couplesmental retardation, in Sidoharjo Village, Jambon District, Ponorogo Regency, which is better known as "Kampung Idiot". The problem that arises from this marriage is how the husband and wife aremental retardation This fulfills the physical and spiritual livelihood. Although husband and wifemental retardation experienced obstacles but the household has survived until now. The resilience of the household is influenced by the pattern of relationships that are established. This study aims to analyze the fulfillment of a living for spousesmental retardation in Sidoharjo Village, Jambon District, Ponorogo Regency, the perspective of gender justice in Islam. The results of this study indicate: Fulfillment of income for families of persons with disabilities in Sidoharjo Village, Jambon District, in terms of gender justice in Islam, is appropriate, in which gender relations are established in fulfilling livelihoods that do not harm either party.